Accountability Effects on Auditors' Performance: The Influence of Knowledge, Problem-Solving Ability, and Task Complexity - Tan, Hun-Tong; Kao, Alison (Journal of Accounting Research, 1999)
Auditing, Knowledge, Problem-Solving Ability, Task Complexity